2017
DOI: 10.1038/ncomms14348
|View full text |Cite
|
Sign up to set email alerts
|

αV-class integrins exert dual roles on α5β1 integrins to strengthen adhesion to fibronectin

Abstract: Upon binding to the extracellular matrix protein, fibronectin, αV-class and α5β1 integrins trigger the recruitment of large protein assemblies and strengthen cell adhesion. Both integrin classes have been functionally specified, however their specific roles in immediate phases of cell attachment remain uncharacterized. Here, we quantify the adhesion of αV-class and/or α5β1 integrins expressing fibroblasts initiating attachment to fibronectin (≤120 s) by single-cell force spectroscopy. Our data reveals that αV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 51 publications
10
90
0
Order By: Relevance
“…The initial step includes the faster adhesion of αV‐class integrins to fibronectin than that shown by α5β1 integrins, which leads to the activation of a group of adhesion‐associated proteins that involved in binding to the Actin cytoskeleton. A consequence of the initial step is the activation of Rac1/Wave/Arp2/3 and RhoA/Rock signaling, which leads to the binding of α5β1 integrins …”
Section: Ecm‐derived Adhesion Moleculesmentioning
confidence: 95%
See 1 more Smart Citation
“…The initial step includes the faster adhesion of αV‐class integrins to fibronectin than that shown by α5β1 integrins, which leads to the activation of a group of adhesion‐associated proteins that involved in binding to the Actin cytoskeleton. A consequence of the initial step is the activation of Rac1/Wave/Arp2/3 and RhoA/Rock signaling, which leads to the binding of α5β1 integrins …”
Section: Ecm‐derived Adhesion Moleculesmentioning
confidence: 95%
“…A recent study revealed the impact of αV‐class integrins on the potent adhesion to fibronectin, which characterized by two main steps . The initial step includes the faster adhesion of αV‐class integrins to fibronectin than that shown by α5β1 integrins, which leads to the activation of a group of adhesion‐associated proteins that involved in binding to the Actin cytoskeleton.…”
Section: Ecm‐derived Adhesion Moleculesmentioning
confidence: 99%
“…The glial scar-inhibitor aggrecan can impair integrin activation (79), which inhibits neurite outgrowth. At the same time, talin binding to integrin tails is a significant step in integrin activation (31), whereas actinin, ICAP-1, filamin, SHARPIN, and DOK1 can compete with talin for binding to integrin (53)(54)(55)(56)(57)(58)(59)61). Therefore, we investigated the connection between the competitive binding proteins of talin and aggrecan stimulation during neuron polarization.…”
Section: Role Of Talin-integrin Signaling In Osmotic Pressurementioning
confidence: 99%
“…Filamin binds to the actin skeleton under tension, resulting in exposure of integrin binding sites, which also induces competitive binding with talin (53)(54)(55). Furthermore, integrin cytoplasmic domain-associated protein-1 (ICAP-1) and docking protein 1 (DOK1) can bind to integrin b through a phosphorylated (p) Y binding domain-Asn-Pro-Xaa-phosphotyrosine (NPxY) interaction (55)(56)(57)(58)(59)(60), and SHANK-associated RH domain interactor (SHARPIN) can bind to the highly conserved WHXGFFKR sequence in the tail of integrin a both of which cause direct competition with talin for integrin b binding (61). Whether this competitive binding affects the chemical and mechanical signals remains unclear.…”
mentioning
confidence: 99%
“…An interaction between uPAR and different integrin subunits, mostly β1, β3 and β6, has been described by biochemical and computational technics [32][33][34][35] . Because the β1 integrin subunit is the receptor for fibronectin [36][37][38] , and since fibronectin is required in our system for uPA/uPAR to promote axonal regeneration, then we postulated that β1 integrin was the co-receptor that mediates the effect of uPA/uPAR on neurorepair. Our hypothesis was further supported by reports from other groups indicating that neuronal β1 integrin expression increases after ischemic stroke [39] and that β1 integrin promotes the regeneration of sensorial axons at long distances in the spinal cord [40] .…”
Section: Membrane Recruitment Of ß1-integrin Mediates Upa/upar-inducementioning
confidence: 99%